Climate-adaptive landscape design: Microclimate and thermal comfort regulation of station square in the Hokuriku Region, Japan. (15th March 2022) - Xiao, Jing; Yuizono, Takaya
Abstract: Strategic landscape design can ameliorate local thermal stress and enhance climate resilience in urban areas. Densely populated station squares are particularly important outdoor activity areas which more require the mitigation of thermal conditions during extreme weather. The traditional station square design focuses on the transport system and lacks the co-regulation of landscape services (e.g., climate change, scale, and element configuration). Moreover, holistic optimal design strategies are still deficient. This study examines how thermal comfort is positively affected by various landscape layout patterns, the configuration ratio of deciduous to evergreen trees and vegetation structure. We selected a typical station square of the Hokuriku region as an example, measured a landscape microclimate environment in winter and summer during extremely cold and hot days. The thermal comfort performance, represented by the Predicted Mean Vote (PMV) thermal index, was compared using the ENVI-met simulation to reproduce the original case and new landscape design scenarios. The results indicated that planting trees in an array layout pattern with low PMV distributions improved thermal performance at 14:00 (0.3 PMV increase in winter and 1.3 PMV decrease in summer). The tree configuration ratio is a critical greening indicator that also regulates thermal comfort during the day and night. The finds of the research can be used optimized scenarios as a guide for urban station square design to mitigate thermal comfort issues and to promote the development of station square planning complying with climate-adaptive design strategies and the construction of sustainable cities. Highlights: ∙ Regulating the tree configuration ratios affects thermal comfort and microclimate, especially during the day and night. ∙ The deciduous to evergreen tree configuration ratio is an important greening indicator for improving winter and summer thermal comfort at the station square. ∙ Evergreen trees have stronger thermal optimization performance than deciduous trees in winter and summer. ∙ Regulation of the landscape design scenarios at a large scale in an array pattern layout can be more effective.